A crise econômica de 2008 nas páginas da Folha de S. Paulo: o conhecimento do jornalismo na era neoliberal - Almeida, Charles Florczak (Universidade do Vale do Rio dos Sinos, 2015)
This paper takes the coverage of Folha de S. Paulo about the economic crisis of 2008 as object for a study of journalism as a form of knowledge. It aimed understand how the coverage of the crisis was carried out from the point of view of the types of content produced, the perspectives and explanations adopted, the political positions defended, in short, the editorial priorities developed by the vehicle. The perspective adopted was that journalism is a form of social knowledge crystallized in the singular, that mediates facts and public, characterized, as knowledge, by its communicability. We argued that social contradictions are shrouded in the journalistic significance process, which justifies a study including informative and opinionated approaches, supporting the essence in the singular. The rise of neoliberalism and its features are understood as hegemonic class project, which is also indicated as explanation matrix for the economic crisis. Economic journalism, in turn, is the space in which it is perceived the relation between journalism and political-economic projects, particularly, neoliberalism, transforming the guidelines and forms of journalism organization. The analysis of the coverage of Folha de S. Paulo includes a corpus of 6,176 journalistic texts of different types and the cover headlines of the 243 issues published by the journal between August 2008 and March 2009, period of accentuation of the crisis, including impacts on Brazilian economy. It was possible to observe the intensity with which the crisis was followed over the weeks, emphasizing the crash of Lehman Brothers as an effective framework of the explosion in the number of news stories. Over the months, there were changes of focus on coverage, especially migrating from the financial market to governments; from abroad to Brazil. The forms developed by economic journalism represent the basic structure of the coverage from the point of view of themes, fonts and other elements. It was identified an emphasis on the duty of the state to solve the problems caused by the crisis, expressing the view of neoliberal orthodoxy as it rests its position in cuts of public spending, liberalization of labor legislation and unquestionable right of companies to dismiss in the political and economic positions taken by newspaper editorials and related to the highlights of cover. It was pointed the greater participation of former members of the government and non-journalists as authors that create the context of the crisis events. There was an emphasis on the point of view of financial market to observe the events and there were generous spaces to business entities, in contrast to what occurs with social movements and worker representation. The economic and the political aspects are interrelated, and journalism has participation in this relation, in the case of crisis, reinforcing the neoliberal hegemonic perspective. It was concluded that, although it is engendered by neoliberal concepts, coverage was developed based on ways of knowing created by journalism.
Keywords: Jornalismo; Jornalismo como conhecimento; Neoliberalismo; Jornalismo de economia; Crise econômica de 2008; Journalism; Journalism as knowledge; Neoliberalism; Economic journalism; Economic crisis of 2008; ACCNPQ::Ciências Sociais Aplicadas::Comunicação